Keanekaragaman Vegetasi Semak di Aliran Air Panas Jaboi Kecamatan Sukajaya Kota Sabang - Hasnatul Salekha; Muslich Hidayat; Mulyadi Mulyadi; Eriawati Eriawati; Cut Ratna Dewi (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2025)
Shrub vegetation is an important component in the structure of vegetation communities that have a significant ecological role, especially in maintaining soil stability and supporting biodiversity. One area that has the potential for shrub vegetation diversity but has not been scientifically documented is the Jaboi hot spring area, Weh Island, Sukajaya District, Sabang City. The purpose of this study was to investigate various types of shrub vegetation found in the study area and to calculate the diversity index. Data collection was carried out using a one-hundred-meter line transect method divided into four paths, with one pair of transects directed towards residential areas and plantation areas, while the remaining two transects were directed towards areas that were still forested. At each transect there were six observation points with a distance between points of 20 meters, each point consisting of three quadrat plots measuring 2 × 2 meters. Analysis of the diversity index used the Shannon-Wiener formula (H’). The results showed that there were 9 shrub species from 7 families with a total of 169 individuals from four observation stations. The Melastomataceae family dominates the shrub community with two main species, Melastoma malabathricum and Memecylon caeruleum. The diversity index value is 2.17, which is included in the moderate category (H = 2–3). This diversity is influenced by the physical-chemical conditions of the environment, such as acidic soil pH (4.4–5.5) and relatively stable temperatures, although temperatures exceeding the optimum limit were found in some locations. This study provides initial data on the potential of shrub vegetation as a basis for ecosystem management and conservation in the area.